Selection for longer lived sperm within ejaculate reduces reproductive ageing in offspring. Issue 2 (14th February 2019) - Alavioon, Ghazal; Cabrera Garcia, Andrea; LeChatelier, Magali; Maklakov, Alexei A.; Immler, Simone
Abstract: Males produce numerous sperm in a single ejaculate that greatly outnumber their potential egg targets. Recent studies found that phenotypic and genotypic variation among sperm in a single ejaculate of a male affects the fitness and performance of the resulting offspring. Specifically, within‐ejaculate sperm selection for sperm longevity increased the performance of the resulting offspring in several key life‐history traits in early life. Because increased early‐life reproductive performance often correlates with rapid ageing, it is possible that within‐ejaculate sperm selection increases early‐life fitness at the cost of accelerated senescence. Alternatively, within‐ejaculate sperm selection could improve offspring quality throughout the life cycle, including reduced age‐specific deterioration. We tested the two alternative hypotheses in an experimental setup using zebrafish Danio rerio . We found that within‐ejaculate sperm selection for sperm longevity reduced age‐specific deterioration of fecundity and offspring survival but had no effect on fertilization success in males. Remarkably, we found an opposing effect of within‐ejaculate sperm selection on female fecundity, where selection for sperm longevity resulted in increased early‐life performance followed by a slow decline, while females sired by unselected sperm started low but increased their fecundity with age. Intriguingly, within‐ejaculate sperm selection also reduced the age‐specific decline in fertilization success in females, suggesting that selection for sperm longevity improves at least some aspects of female reproductive ageing. These results demonstrate that within‐ejaculate variation in sperm phenotype contributes to individual variation in animal life histories in the two sexes and may have important implications for assisted fertilization programs in livestock and humans.